Design of a Submarine Vehicle for Higher Natural Frequency Using U∗ Index Theory Approach - Weiyan Shang; Qingguo Wang (Shock and Vibration)
The natural frequency of a vehicle structure should be far higher than the road excitation frequency in order to avoid dynamic problems caused by structural resonance. Submarine vehicles or robots are facing the same issue as mentioned above. This paper proposed a means to effectively increase the natural frequency of submarine vehicles or robots by using U∗ index approach. The U∗ theory was originally introduced to investigate load transfer paths within a structure. It is a new design paradigm for vehicle structures. In this study, the U∗ index theory was applied to evaluate the internal stiffness distribution of a submarine vehicle structure and then a modified design was achieved based on the U∗ analysis. Compared to the original design, the natural frequency of the modified vehicle structure was increased by more than 40% while the weight of the modified vehicle was only raised by 4.6%.